(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
This study analyzes Saudi Arabia’s innovation performance over 12 years, using the Global Innovation Index (GII) to compare it with G20 countries. Innovation, essential for economic growth and competitiveness, is measured through input and output scores by the GII. Despite substantial investments, Saudi Arabia’s innovation performance has fluctuated, showing growth from 2012 to 2014, a decline from 2014 to 2020, and a slow recovery from 2020 to 2023. Secondary data from GII reports were analyzed using E-views for Pearson correlation matrix calculations and DEA software for Data Envelopment Analysis. The findings reveal Saudi Arabia’s commitment to innovation, evidenced by consistent investment in research and development. While the country’s innovation ecosystem demonstrates room for improvement in converting inputs into tangible outcomes, Saudi Arabia shows a moderate positive correlation between inputs and outputs. The study highlights the need for Saudi Arabia to optimize strategies and processes to enhance Innovation efficiency. By benchmarking with high-efficiency G20 countries, Saudi Arabia can improve its innovation ecosystem and boost overall competitiveness and economic growth. This research is valuable for further studies and provides a foundation for policymakers and researchers to develop targeted strategies for sustained innovation performance improvements, aiming for a more robust and effective innovation system.